Core–shell CoFe2O4@Co–Fe–Bi nanoarray: a surface-amorphization water oxidation catalyst operating at near-neutral pH. Issue 23 (31st May 2017) - Ji, Xuqiang; Hao, Shuai; Qu, Fengli; Liu, Jingquan; Du, Gu; Asiri, Abdullah M.; Chen, Liang; Sun, Xuping
Abstract : Core–shell CoFe2 O4 @Co–Fe–Bi nanoarray on carbon cloth (CoFe2 O4 @Co–Fe–Bi/CC) acts as a durable water oxidation electrocatalyst with an overpotential of 460 mV to drive 10 mA cm −2 in 0.1 M potassium borate (pH 9.2). Abstract : The exploration of high-performance and earth-abundant water oxidation catalysts operating under mild conditions is highly attractive and challenging. In this communication, core–shell CoFe2 O4 @Co–Fe–Bi nanoarray on carbon cloth (CoFe2 O4 @Co–Fe–Bi/CC) was successfully fabricated by in situ surface amorphization of CoFe2 O4 nanoarray on CC (CoFe2 O4 /CC). As a 3D water oxidation electrode, CoFe2 O4 @Co–Fe–Bi/CC shows outstanding activity with an overpotential of 460 mV to drive a geometrical catalytic current density of 10 mA cm −2 in 0.1 M potassium borate (pH 9.2). Notably, it also demonstrates superior long-term durability for at least 20 h with 96% Faradic efficiency. Density functional theory calculations indicate that the conversion from OOH* to O2 is the rate-limiting step and the high water oxidation activity of CoFe2 O4 @Co–Fe–Bi/CC is associated with the lower free energy of 1.84 eV on a Co–Fe–Bi shell.